Potential of chitosan as anti Candida albicans in denture bases made from thermoplastic nylon - Helmi Fathurrahman; Muvida Savitri Listyastuti; Niluh Ringga Woroprobosari; Teguh Tri Widodo (Odonto : Dental Journal, 2023)
Background: Candida albicans is main cause of fungal infections in denture users. Prevention is needed by soaking dentures using a disinfectant. Chitosan is an alternative disinfectant emulsion because it is biodegradable, biocompatible, and does not cause discoloration. This research objective is to determine the effect of chitosan emulsion on the number of C.albicans on base plate thermoplastic nylon. Method: This is a true experimental study using post-test only design by using 25 base plates divided into 5 groups namely treatment I, treatment II, treatment III, positive and negative control. Plate was incubated in C.albicans suspension for 24 hours in McFarland and 10-3 series dilution. The plates was rinsed with aquadest, then soaked with 0.3% chitosan emulsion, 0.8% chitosan emulsion, 2% chitosan emulsion, 0.2% chlorhexidine gluconate, and aquadest for 15 minutes. The attached C.albicans colony in the plate was released to the SDB by using centrifuge device, then proliferated on the SDA and incubated (24 hours). The results of the C.albicans colony were counted visually by using a colony counter. The number of Candida albicans colonies data were analyzed using One-Way ANOVA and then Post Hoc Tukey HSD test. Result: The results showed that there were significant mean differences between each group (p